Hematite Thin Films with Various Nanoscopic Morphologies Through Control of Self-Assembly Structures - Liu, Jingling (Nanoscale Res Lett, 2015)
Hematite (α-Fe(2)O(3)) thin films with various nanostructures were synthesized through self-assembly between iron oxide hydroxide particles, generated by hydrolysis and condensation of Fe(NO(3))(3) · 6H(2)O, and a Pluronic triblock copolymer (F127, (EO)(106)(PO)(70)(EO)(106), EO = ethylene oxide, PO = propylene oxide), followed by calcination. The self-assembly structure can be tuned by introducing water in a controlled manner through the control of the humidity level in the surrounding of the as-cast films during aging stage. For the given Fe(NO(3))(3) · 6H(2)O:F127 ratio, there appear to be three different thermodynamically stable self-assembly structures depending on the water content in the film material, which correspond to mesoporous, spherical micellar, and rod-like micellar structures after removal of F127. Coupled with the thermodynamic driving forces, the kinetics of the irreversible reactions of coalescence of iron oxide hydroxide particles into larger ones induce diverse nanostructures of the resultant films. The length scale of so-obtained nanostructures ranges from 6 nm to a few hundred nanometers. In addition to water content, the effects of other experimental parameters such as aging temperature, spin rate during spin coating, type of substrate, and type of iron reagent were investigated. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-015-0936-x) contains supplementary material, which is available to authorized users.